Analysis of political and diplomatic language in linguistic, cognitive and pragmatic aspects - Kalbike Yessenova, Fariza Ismailova, Gulzat Rayeva, Aiman Koblanova, Bauyrzhan Yelikbayev, (Opción, 2020)
The study aims to investigate the analysis of political and diplomatic language in linguistic, cognitive and pragmatic aspects via comparative qualitative research methods. As a result, the creation of the meaning of the English diplomatic terms in the singular is similar to the creation of the meanings of the original words and have different meanings, but their terminological or non-terminological meaning is determined by the context. In conclusion, the metaphorization of figurative and abstract concepts of the Kazakh political language is a tradition that came from the ancient Turkic worldview.